Vertical integration and performance in marketing channels - Childerley, Angela M. (Cranfield University, 1980)
Since the late 1960's there has been an increasing tendency to analyse marketing channels as social systems rather than as economic systems. Despite this, the relationship between vertical integration and performance in marketing channels has continued to be analysed from an economic perspective. In this study, not only is a social systems approach adopted to examine the relationship between vertical integration and performance, but certain additional features are also included to refine this approach. There are a variety-of social systems, each with distinct characteristics. This study argues that the marketing channel can be interpreted as an Interorganisational Collectivity, a form of interorganisational system. The model of vertical integration and performance that is proposed, and subsequently examined, is based on a combination of theoretical and empirical analysis. This work involved a series of in-depth interviews, reference to studies of interorganisational networks other than marketing channels, and a consideration of certain behavioural themes from the channels literature. In addition to the social systems approach, this model differs from previous models in several other respects. These are the separation of vertical integration and co-ordination, -the multi-dimensional view of channel performance and the introduction of channel atmosphere as a principal factor. A detailed analysis of marketing channels in the egg industry is used to test the appropriateness of the model, and to identify some modifications to its operational elements. These modifications allow for further validation to take place. Although the empirical examination of the model was affected by a fundamental reorganisation within the industry during the course of the work, the results do serve to indicate the usefulness of the concept of channel atmosphere and the need to take account of the size of channel members whenever the. relationship between vertical integration and performance is considered.